KERENTANAN DAERAH PESISIR AKIBAT NAIKNYA MUKA AIR LAUT (SEA LEVEL RISE) DI INDONESIA - Nur Haslinda; Iqra Shakira Maharani (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2025)
Rising sea levels pose a serious threat to Indonesia, this country has the largest archipelago in the world. This is caused by global warming and melting ice at the poles which will cause a rise in global sea levels of up to 0.26-0.77 meters or more in 2100. This increase has a significant impact on Indonesia's coastal areas, including the decline of coastlines, inundation, sea ​​water intrusion, and other threats. This study aims to identify the coastal areas most vulnerable to sea level rise in Indonesia, as well as the factors that influence it. The results of this research help in developing mitigation and adaptation policies to deal with global climate change. The research method used is a literature study with a descriptive approach, this involves mapping the geophysical and socio-economic vulnerability of coastal areas. Mitigation efforts include developing coastal area spatial planning that takes into account the potential for sea level rise, increasing public awareness, sustainable management of natural resources, development of disaster-resistant infrastructure, and international cooperation. This information is important in protecting Indonesia's coastal ecosystems, economy and society from the impacts of rising sea levels.